Rapid and nondestructive techniques for internal and external quality evaluation of watermelons: a review - Mohd Ali, Maimunah; Hashim, Norhashila; Bejo, Siti Khairunniza; Shamsudin, Rosnah (Elsevier B.V, 2017)
Watermelon has emerged to the forefront in research advances due to its attractive high nutrient value. Quality attribute of watermelon is a critical aspect of postharvest storage, consumer preference, and commercial acceptability of the fruit. The promising technologies of quality evaluation using nondestructive techniques as part of postharvest handling have gained much attention in recent years. The current trends seek nondestructive techniques that are rapid, low cost, and provide objective measurements. This review highlights some recent applications of nondestructive techniques in the quality evaluation of watermelon by replacing conventional methods which are time-consuming, laborious, and tedious. Quality assessment of watermelons, especially during harvesting and sorting/grading processes, is discussed in this paper, focusing specifically on the feasibility of its application and performance by providing a real-time, rapid and efficient approach. The advantages and drawbacks of nondestructive techniques are emphasized for evaluating quality attributes of the fruit. The future prospects of using nondestructive techniques for quality evaluation have proven to be successful in the development of an automated sorting machine and an on-line detection system.